Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1999
DOI: 10.1115/99-gt-169
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Flow on the First Stage Blade Tip of a Power Generation Gas Turbine: Part 1 — Experimental Results

Abstract: A combined experimental and computational study has been performed to investigate the detailed distribution of convective heat transfer coefficients on the first stage blade tip surface for a geometry typical of large power generation turbines (>100MW). This paper is concerned with the design and execution of the experimental portion of the study, which represents the first reported investigation to obtain nearly full surface information on heat transfer coefficients within an environment which develops an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Bunker et al [2] presented detailed tip heat transfer measurements. They observed that reduced tip clearances can reduce heat transfer and located areas of high heat transfer.…”
mentioning
confidence: 99%
“…Bunker et al [2] presented detailed tip heat transfer measurements. They observed that reduced tip clearances can reduce heat transfer and located areas of high heat transfer.…”
mentioning
confidence: 99%
“…The experimental setup and conditions are similar to those described in [3]. In that paper the pressure distribution and tip heat transfer for both a sharp edge tip and radiused edge tip of the present blade geometry were presented.…”
Section: The Experimental Setupmentioning
confidence: 91%
“…This has spurred experimental work on measuring tip heat transfer for various blade tip treatments on stationary cascades and has provided data for numerical simulations. In a previous numerical study [2] the predicted tip heat transfer for a sharp edge tip and a radiused tip (blade tip with a rounded edge around the perimeter of the blade tip) was compared with the measured experimental data of Bunker et al [3]. The data was, at the time, the only set of liquid crystal measurements of tip heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called "sweet spot" has been observed by Bunker et al [22], whose study was conducted at flow conditions of exit Mach 0.75 with varying turbulent intensities of five and nine percent. In the present study, the "sweet spot" region is larger for the lower tip gap cases of 0.9%.…”
Section: Flow Visualizationmentioning
confidence: 93%